Physicochemical and Sensory Characteristics of Bread Substituted with Dragon Fruit Peels - Mohd Razip, Nur Haziqah; FMNA, Aida; Siva Manikam, Raseetha Vani; Gandaseca, Seca (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Dragon fruit peel (DFP) which is typically discarded can provide a substantial amount of naturally occurring nutrients in low-fibre commercial white bread. The study evaluated physicochemical and sensory analysis of dragon fruit peel flour (DFPF) as a partial substitute for wheat flour in white bread formulations in following proportions: 0%, 3%, 6% and 9% (w/w). The measurements of the substituted breads involved crude fibre, ash, crude protein, fat, carbohydrate, moisture, volume, texture profile and colour profile along with sensory analysis. Based on chemical composition, DFPF was high in ash (11.60%), crude fibre (25.48%) and carbohydrate content (48.58%) however it was low in moisture (9.31%), fat (0.83%) and crude protein (5.15%). DFPF exhibits a brighter red colour due to the high values of L* and a*. As the DFPF level increased, the bread's ash and crude fibre content increased significantly, however the amount of carbohydrates decreased significantly. The bread's volume declined, while its moisture, density and hardness increased. Through sensory evaluation, the 6% DFPF was most favourable in terms of its appearance and texture. The addition of DFPF did not adversely affect the general appeal of the bread, indicating that it is a feasible way to increase the nutritious content of bread. In conclusion, DFPF can be used as a partial flour substitute to increase the nutritional value of white bread, particularly by increasing crude fiber content. The 6% substitution level provided the best balance of nutritional enhancement and consumer acceptance, indicating its potential for use in functional bakery goods.